Effect of Trichoderma spp. isolates for biological control of tan spot of wheat caused by Pyrenophora tritici-repentis under field conditions in Argentina - Perelló, Analía Edith (2008)
Trichoderma spp. have been used as biocontrol agents to protect plants against foliar diseases in several crops, but information from field assays is scarce. In the present work, experiments were carried out to determine the effect of six isolates of Trichoderma harzianum and one isolate of T. koningii on the incidence and severity of tan spot, caused by Pyrenophora tritici-repentis (anamorph: Drechslera tritici-repentis) under field conditions. Significant differences between years, wheat cultivars and treatments were found. In 2003, two of the isolates assayed (T5, T7) showed the best performance against the disease applied as seed treatments or sprayed onto wheat leaves at different stages. The application of six of the treatments on wheat plants significantly reduced disease severity by 16 to 35% in comparison with the control. Disease control provided by isolate T7 was similar to that provided by the fungicide treatment (56% reduction). This is the first report on the efficacy of Trichoderma spp. against tan spot under field conditions in Argentina.